Portrayal of women in Amitav Ghosh’s Novels Sea of Poppies and River of Smoke - Islam, Tasmeyah Mahbuba (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.